Espécies do gênero Eimeria Schneider, 1875, (Apicomplexa: Eimeriidae) parasitos de caprinos leiteiros no município de Afonso Bezerra, Rio Grande do Norte - Avelino, Danielly Bezerra (Universidade Federal Rural do Semi-Árido, 2010)
The gastrointestinal parasites are major obstacle to a goat, with emphasis on eimeriosis considered limiting factor for the exploitation of these animals. Thus, species of the genus Eimeria were studied in dairy goats in a production unit of the municipality of Afonso Bezerra, Rio Grande do Norte, from March 2008 to February 2009. Of the 600 stool samples examined both goat females as young adults, were positive for the presence of Eimeria often respectively 62.2% and 37.8%. Based on the morphology of the oocysts were identified nine species of Eimeria at a higher frequency of E. ninakolhykimovae (28.42%) in young, unlike adults, where he highlighted the E. apsheronica (26.66%). Moreover, were also identified as E. alijevi, E. arloingi, E. hirci, E. jolchijevi, E. christenseni, E. caprovina and E. goats. Regarding the effect of the development phase of the host in morphometric measurements of oocyst and sporocyst species E. alijevi, E. arloingi and E. ninakolhykimovae significant effect (P <0.01) for the major and minor diameters of the oocyst and sporocyst. Already the species E. hirci was significant (P <0.01) only for the major and minor diameters of the sporocyst. For E. jolchijevi was significant (P <0.01) increased the diameter of the sporocyst and the E. apsheronica, only the smaller diameter of the oocyst.
Species of gender Eimeria Schneider, 1875, (Apicomplexa: Eimeriidae) parasites of goats in the municipality of dairy Afonso Bezerra, Rio Grande do Norte
Keywords: Goats; Eimeria; Morphometry; Frequency; Caprino; Eimeria; Morfometria; Frequência; CIENCIAS AGRARIAS::MEDICINA VETERINARIA